Scaling Up Quality Infrastructure Investment. (Washington, D.C. : International Monetary Fund, 2021)
South Asia needs large infrastructure investments to achieve its development goals, and public investment can also support the Covid-19 recovery. Regression estimates that account for the quantity and quality of investment suggest that public infrastructure was a key driver of productivity growth in South Asia. Going forward, higher public infrastructure spending can raise growth, but its benefits depend on how it is financed and managed. Model simulations show that tax financing, concessional lending, or private sector financing through public private partnerships (PPPs) are more advantageous than government borrowing through financial markets because they support growth while containing the impact on public debt. However, the optimal choice also depends on available fiscal space, taxation capacity, implementation risks, and public investment efficiency. To reap the most benefits from higher infrastructure investment, South Asian countries need to manage fiscal risks carefully, including from PPPs and state-owned enterprises, and improve public investment efficiency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; Informal Economy; National Government Expenditures and Related Policies; Other Public Investment and Capital Stock; Underground Econom